Desempenho e parâmetros do metabolismo protéico de bovinos criados a pasto e suplementados no período da seca com ureia convencional e/ou ureia de liberação lenta - Patricia Caires Molina (2012)
Intake, weight gain, plasma urea nitrogen (PUN) and urinary biochemical profile of cattle raised on Brachiaria brizantha. Marandu and supplemented during the dry season with conventional urea and / or urea slow release. The treatments were: SM (Mineral Supplement; mineral salt 0% urea); U: (Mineral Supplement Protein, 6% urea), O: (Mineral Supplement Protein, 6% Optigen ®), OU: (Mineral Supplement Protein; 3% + 3% urea Optigen ®) with average intake of 1 kg / head / day. 40 steers were used to evaluate the weight gain and concentration of PUN. For evaluation of total dry matter intake (CSMT) used 20 steers were randomly selected (5 for each treatment). For the evaluation of biochemical urinary 15 animals were utilized (3 animals in group SM; 4 animals in group U; 4 animals in group 4 animals and the group OU) chosen at random. The total dry matter intake in relation to the percentage of body weight (% BW) of the supplemented groups did not differ (P> 0.05), and also did not differ from the SM group (P> 0.05). There was no difference in average daily gain (ADG) and total weight gain (TWG) between the supplemented groups (P> 0.05) ADG values being 0.327 kg, 0.316 kg and 0.286 kg, respectively for treatments OU, U and O. The SM group lost weight during the whole experimental period presenting value of -0.124 kg/day. The concentration of PUN before the supply of the supplement did not differ between treatments. Four hours after supplementation, the group U showed a peak of NUP, different (P> 0.05) of treatment SM. Eight hours after feeding treatment OU peaked at NUP, different (P> 0.05) in the SM group. Twenty hours later, there was no difference between groups. The excretion of urea SM group was lower than in groups U and O (P <0.05). The values found creatinine were not different (P> 0.05) among treatments. The uric acid values ranging from 9.41 to 23.35 mmol / day and did not differ between treatments. The values of allantoin excretion did not differ (P> 0.05) among treatments, indicating that there was no effect of supplemental nitrogen in the proportions studied on rumen microbial production.